PENGARUH DIGITAL MARKETING, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN COFFE SHOP DI CIKARANG - Alfina Damayanti; Elsa Nurcholisa; Siti Dewiningsih Alawiyah; Ahmad Gunawan (MANAJEMEN DEWANTARA, 2023)
The research was conducted to determine the effect of digital marketing,promotion, and quality of service on consumer decisions to purchase at a coffee shop in Cikarang. In this research, the researcher uses the Lemeshow formula in determining the sample. The data used is primary data which is obtained by the author through a questionnaire distributed to 100 respondents. The significant effect of X1 and Y variables is 4.092 from the table value 1.66071 with a significant number 0.000 <0.05, the significant effect of the variable X2 and Y are worth 0.500 > 1.66071 with a significant number of 0.618 > 0.05 and the significant effect of X3 and Y variables is 8.084 from the table value of 1.66071 with a significant number of 0.000 < 0.005. The influence of the simultaneous variables X1, X2, X3 on Y is 72.748 > 2.7 which has a greater meaning than F table which means that there is an influence between digital marketing, promotion, and service quality on purchasing decisions at a coffee shop in Cikarang.